The making of a mystic : new and selected letters of Evelyn Underhill - Underhill, Evelyn, 1875-1941.; Poston, Carol, 1943- (Urbana : University of Illinois Press, 2010)
"Evelyn Underhill (1875-1941) achieved international fame with the publication of her book Mysticism in 1911. Continuously in print since its original publication, Mysticism remains Underhill's most famous work, but in the course of her long career she published nearly forty books, including three novels and three volumes of poetry, as well as numerous poems in periodicals. She was the religion editor for Spectator, a friend of T.S. Eliot (her influence is visible in his last masterpiece, Four Quartets), and the first woman invited to lecture on theology at Oxford University." "In time for the centennial celebration of her classic Mysticism, this volume of Underhill's letters will enable readers and researchers to follow her as she reconciled her beliefs with her daily life. The letters reveal her personal and theological development and clarify the relationships that influenced her life and work. Drawing from collections previously unknown to scholars, The Making of a Mystic shows the range of Evelyn Underhill's mind and interests as well as the immense network of her correspondents, including Sir James Frazier and Nobel Prize laureate Rabindranath Tagore. This substantial selection of Underhill's correspondence demonstrates an exceptional scope, beginning with her earliest letters from boarding school to her mother and extending to a letter written to T.S. Eliot from what was to be her deathbed in London in 1941 as the London Blitz raged around her."--Jacket.
Introduction -- A note on editorial practice -- The early years : 1888-1905 -- Toward mysticism : 1906-10 -- A dark time : 1911-23 -- The retreat years : 1924-34 -- Worship unto death : 1935-41.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Underhill, Evelyn, -- 1875-1941 -- Correspondence; Underhill, Evelyn, -- 1875-1941; Underhill, Evelyn; Mystics -- England -- Correspondence; Mystiques -- Angleterre -- Correspondance; LITERARY COLLECTIONS / General; Mystics; England; Briefsammlung 1888-1941.; Personal correspondence